THU0277 Epratuzumab: Sustained Safety Profile and Effect on Corticosteroid Use on Long-Term Treatment in Patients with Moderate-to-Severe Systemic Lupus Erythematosus: Results from an Open-Label Long-Term Extension Study (Sl0008). (23rd January 2014) - Wallace, D. J.; Ordi-Ros, J.; Neuwelt, M.; Kalunian, K.; Kilgallen, B.; Bongardt, S.; Petri, M.; Pike, M.; Jeka, S.; Gordon, C.; Strand, V.
Abstract : Background: The safety and efficacy of epratuzumab, a monoclonal antibody targeting CD22, were assessed in EMBLEM™, a 12-week phase IIb study in patients with moderate-to-severe systemic lupus erythematosus (SLE). 1 SL0008 (NCT00660881 ) was an open-label extension of EMBLEM™. Objectives: To evaluate the safety profile and effect on corticosteroid (CS) use of long-term epratuzumab treatment in patients with moderate-to-severe SLE. Methods: EMBLEM™ patients who completed 12 weeks' blinded treatment and patients who discontinued due to lack of efficacy but completed ≥8 weeks were eligible for SL0008. Patients received 1200 mg epratuzumab at weeks 0 and 2 of 12-week cycles. Study entry was SL0008 week 1. Evaluation visits were at weeks 4 and 8 of each cycle. Safety variables included duration of exposure, adverse events, infusion reactions and infections. CS doses were monitored throughout and converted to prednisone equivalent dose before analysis. Data are summarized using descriptive statistics. Results: 203 patients received a median 845 (range 75–1185) days' exposure to epratuzumab over a median 10 treatment cycles (range 1–14). Median CS dose was 10.0mg/day at EMBLEM™ baseline and SL0008 screening, and 5.0mg/day at week 116 (n=112; last timepoint with >50% of patients reporting this endpoint). The proportion of patients requiring 7.5–20mg/day and >20mg/day decreased from 49.8% and 10.8% at SL0008 baseline to 33.9% and 8.0% at week 116, respectively. Conversely, the proportion of patients receiving only >0–7.5mg/day or not receiving any CS increased from 33.5% and 5.9% to 45.5% and 12.5%, respectively. Adverse events (AEs) were reported by 192 (95%) patients and investigator-assessed as related to study drug in 87 (43%) patients. The most common SAEs and infections/infestations are summarized in the Table. There were no opportunistic infections (risk of infections/infestations did not increase during the study), and no patterns of specific serious (n=14 [6.9%]) or severe (n=10 [4.9%]) infections. There was no indication of an increased risk of malignancies. One patient died of cardiac failure, deemed unlikely to be treatment-related. Conclusions: Long-term treatment with epratuzumab in the SL0008 study was associated with decreases in CS use in those receiving >7.5mg/day. Epratuzumab had an acceptable safety profile, with no new safety signals identified. References: Wallace DJ, et al. Ann Rheum Dis, Online First 12 January 2013. DOI: 10.1136/annrheumdis-2012-202760. Disclosure of Interest: D. Wallace Consultant for: Bristol-Myers Squibb, Genentech, Biogen IDEC Inc, GlaxoSmithKline, Human Genome Sciences Inc, MedImmune, Novo Nordisk, UCB Pharma, J. Ordi-Ros: None Declared, M. Neuwelt: None Declared, K. Kalunian Consultant for: Bristol-Myers Squibb, Genentech and Biogen IDEC Inc, Anthera, MedImmune, Novo Nordisk, Zymogenetics, Serono and UCB Pharma, and received research grants from Genentech and Biogen IDEC Inc, Cephalon, Cypress, MedImmune, Novo Nordisk and UCB Pharma, B. Kilgallen Shareholder of: UCB Pharma, Employee of: UCB Pharma, S. Bongardt Employee of: UCB Pharma, M. Petri Grant/research support from: UCB Pharma, Consultant for: UCB Pharma, M. Pike Consultant for: UCB Pharma, S. Jeka: None Declared, C. Gordon Grant/research support from: Aspreva, Consultant for: Aspreva, Bristol-Myers Squibb, Genentech and Biogen IDEC Inc, Merck Pharmaceuticals, Roche and UCB Pharma, V. Strand Consultant for: UCB Pharma, Abbott Immunology Pharmaceuticals, Amgen Inc., AstraZeneca, Biogen Idec, Canfite Pharma, Centocor, Inc., Cypress Biosciences, Inc., Euro-Diagnostica Inc., Fibrogen, Forest Laboratories, Genentech and Biogen IDEC Inc., Human Genome Sciences, Inc., Incyte, Novartis Pharmaceuticals Corporation, Alder, CBio, Chelsea, Crescendo, Idera, Jazz Pharmaceuticals, Lexicon Genetics, Logical Therapeutics, Lux Biosciences, NovoNordisk, Nuon, Ono, SKK, Pfizer Inc., Rigel Pharma, Roche, sanofi-aventis, Savient Pharmaceuticals and Schering-Plough.